Integrating Technology in Mathematics Education: Expanding a Boundary of Transformative Learning - Dahal, Niroj; Lamichhane, Basanta Raj (Mathematics Education Forum Chitwan, 2025)
Mathematics education evolves in conjunction with human civilization, scientific inquiry, technological advancements, and ontological-epistemic practices. This editorial examines five distinct yet interconnected research studies that collectively support the advancement of our understanding of effective mathematics education. Through examining 3D visualization technologies in differential geometry, teacher agency within centralized curriculum reforms, the psychological construct of mathematics self-efficacy, the historical evolution of summability methods, and metacognitive awareness across linguistic contexts, we illuminate the multidimensional nature of mathematics education research. These studies have employed diverse methodological traditions, ranging from design-based research and narrative inquiry to systematic reviews and historical analysis, to illuminate how technological pedagogical content knowledge, transformative praxis, and learner-centered approaches contribute to enhancing mathematical understanding. The synthesis features that meaningful mathematics learning emerges through the integration of technology with carefully orchestrated experiences that develop students' cognitive schemas, teachers' professional knowledge and skills, and the historical development of the disciplines. In this context, this editorial calls for the continued integration of technology-enhanced visualization to empower teachers and students' learning agency, cultivate learner self-efficacy for developing an engaged learning culture, and develop metacognitive competencies as essential components of transformative mathematics education.